2019
DOI: 10.1002/aenm.201901065
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Temperature Reduction Strategy Synthesized Si/Ti3C2 MXene Composite Anodes for High‐Performance Li‐Ion Batteries

Abstract: Silicon is attracting enormous attention due to its theoretical capacity of 4200 mAh g−1 as an anode for Li‐ion batteries (LIBs). It is of fundamental importance and challenge to develop low‐temperature reaction route to controllably synthesize Si/Ti3C2 MXene LIBs anodes. Herein, a novel and efficient strategy integrating in situ orthosilicate hydrolysis and a low‐temperature reduction process to synthesize Si/Ti3C2 MXene composites is reported. The hydrolysis of tetraethyl orthosilicate leads to homogenous nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
229
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 309 publications
(234 citation statements)
references
References 61 publications
5
229
0
Order By: Relevance
“…Subsequently, SiO 2 nanoparticles are reduced to Si via a low-temperature reduction route. [79] In Situ Polymerization: Conductive polymers have shown great potential in electrochemical energy storage due to their large surface area, structural tunability and high redox activity. The combination of conductive polymers and MXenes is promising to construct nanocomposites with higher electrochemical performance due to their synergistic effect.…”
Section: In Situ Carbonizationmentioning
confidence: 99%
“…Subsequently, SiO 2 nanoparticles are reduced to Si via a low-temperature reduction route. [79] In Situ Polymerization: Conductive polymers have shown great potential in electrochemical energy storage due to their large surface area, structural tunability and high redox activity. The combination of conductive polymers and MXenes is promising to construct nanocomposites with higher electrochemical performance due to their synergistic effect.…”
Section: In Situ Carbonizationmentioning
confidence: 99%
“…MXene, an intriguing member of 2D nanomaterial family, is endowed with the amalgamation of superior electrical conductivity, large specific surface area, and hydrophilic surfaces, and has been widely used in Li‐ion batteries, electrochemical storage systems, electromagnetic interference shielding, electrocatalysts, photo‐to‐thermal conversion, etc. Up to now, over 20 species of 2D MXenes have been reported .…”
Section: Introductionmentioning
confidence: 99%
“…Hui et al. demonstrated that Ti 3 C 2 hosts can significantly boost the rate capability and cycling durability of Si NPs …”
Section: Methodsmentioning
confidence: 99%
“…[9b] Hui et al demonstrated that Ti 3 C 2 hosts can significantly boost the rate capability and cycling durability of Si NPs. [13] Ma et al prepared MoS 2 -in-Ti 3 C 2 composites through electrostatic adsorption followed by ac etrimoniumb romide (CTAB)regulated growth. [12] The as-derivedM oS 2 -in-Ti 3 C 2 electrode delivered ah igh capacity of 340 mAh g À1 even at 20 Ag À1 and a satisfactory lifetime, but only under al ow MoS 2 content of approximately 50.3 wt %.…”
mentioning
confidence: 99%